Fruit maturity, seed treatment and storage of Coffea liberica Hiern - Abd Rahman, Faizah Salvana (2018)
Coffee seeds obtained through conventional methods performed poorly in the field with very slow and asynchronous germination. Harvesting at the right stage of maturity may result to improve the performance of seeds during the rootstock development. This study was carried out to determine the suitable fruit maturity stages for seeds to be used in seedling establishment, to determine the effect of various seed pretreatments to obtain a rapid germination rate and to establish an appropriate drying and storage method for Coffea liberica. The first part of study was conducted to assess the germination ability of seven different C. liberica clone seeds namely MKL 1, MKL 2, MKL 3, MKL 4, MKL 5, MKL 6 and MKL 7. The results revealed that seeds from MKL 5 had the highest germination percentage (GP) of 93%, germination index (GI) of 0.97 and mean germination time of 29 days, while seeds from MKL 3 had the lowest with 70% germination percentage (GP), 0.62 germination index (GI) and mean germination time (MGT) 35 days.